Pengaruh Durasi Radiasi UVC Terhadap Nilai Total Plate Count (TPC) CILOK (Effect of UVC Radiation Duration on The Total Plate Count (TPC) of CILOK) - Wulan Fitriani Safari; Dania Febriani Fariska; Mohamad Syafaat (Politeknik Kesehatan Kementerian Kesehatan Banten, 2025)
Cilok is a popular street food enjoyed by various groups, but it carries a high risk of microbial contamination. One of the parameters used to assess food safety is the Total Plate Count (TPC), with a maximum limit of 1 × 10⁵ CFU/g according to BPOM standards. UVC irradiation can be applied to reduce microbial contamination in cilok. The effectiveness of UVC radiation in inactivating bacteria is influenced by several factors, such as wavelength, distance from the light source, and exposure duration. This study aims to determine whether the duration of UVC radiation affects the TPC value of cilok. Cilok samples were collected from street vendors around Binawan University and exposed to UVC radiation for 0 minutes (control), 30 minutes, and 60 minutes. TPC testing was conducted using the Pour Plate method. The results showed that UVC radiation treatment reduced the TPC value of cilok. The highest TPC value was found in the untreated sample (1.8 × 10⁶ CFU/g), followed by samples exposed for 30 minutes (4.5 × 10⁵ CFU/g) and 60 minutes (2.1 × 10⁴ CFU/g). One-way ANOVA analysis indicated a significant difference among treatment groups (p < 0.05), suggesting that UVC radiation duration has a significant effect in reducing microbial counts in cilok.